Book Writing Training for Young Educators of FKIP, University of Bengkulu - Sary, Fetty Poerwita; Dudija, Nindya; Prasetio, Adhi (Edumedia Solution, 2025)
Not all educators have sufficient skills and experience in writing books, especially for young educators who are still in the early stages of their academic careers. To overcome these problems, a training program is needed that can provide an in-depth understanding of effective book writing techniques and strategies as well as assistance in the compilation process. Therefore, this Community Service activity is designed to provide book writing training to more than 60 young educators at the FKIP, University of Bengkulu with methods that include lectures, demonstrations, and Question and Answers sessions. To measure the effectiveness of this activity, we employ Mann-Whitney test procedure. The training proven to have significant improvement effect on the participants score results of their book writing knowledge.